Effect of Different Organic Substrates and Plant Botanicals on Growth and Flowering of Chincherinchee (Ornithogalum thyrosides jacq) - Sharma, Milan; Rana, Manju; Sharma, Puscal; Das, Shaon Kumar (Indian Journal of Hill Farming, 2017)
A pot experiment was conducted to investigate the effect of different organic substrates and plant botanicals on the growth and flowering of chincherinchee under Sikkim agro-climatic condition. Four different organic substrate i.e. FYM, sewage sludge compost, vermicompost and spent mushroom compost, along with foliar spray of cow urine either alone, or with plant extract of neem and Artemisia was used. Maximum plant height (35.27 cm), leaf area (131.60 sq. cm) and total number of opened floret (59.44) was recorded in treatment soil + sewage sludge compost (1:1 v/v) + cow urine + Artemisia @ 10 % at every 15 days interval. Maximum number of leaves (10.22), minimum days for floret opening and maximum spike yield was also found on treatment soil + sewage sludge compost (1:1 v/v) + cow urine + Artemisia. Maximum rachis length and vase life was recorded in soil + sewage sludge compost (1:1 v/v) + cow urine + Artemisia). For better vegetative growth and flowering of potted chincherinchee FYM and sewage sludge compost with a foliar spray of cow urine with extraction of Artemisia are facilitated beneficial.